Imagining Youth Futures University Students in Post-Truth Times - Black, Rosalyn; Walsh, Lucas; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book offers a much-needed analysis of how young people understand and navigate their lives as workers, family members and political actors in an era of uncertainty, Brexit and Trump. Drawing on the latest and most seminal international research and the unique stories of 30 young university students from Australia, France and Britain, it explores the nature of higher education and post-education trajectories for young people facing a 'post-truth' world in which opportunities for home ownership, work security and the formation of committed relationships have been thoroughly eroded. It also presents a timely reflection on young people's hopes and concerns in the wake of global political upheaval, demographic change, financial crises, labour market uncertainties and unprecedented human mobility. Imagining Youth Futures makes a unique contribution to the fields of youth studies, transitions to university, and contemporary youth patterns in the areas of work, family, politicsand mobility.
1. Introduction -- 2. A Brief History of Youth -- 3. Political Citizenship -- 4. Higher Education and Citizenship -- 5. Cultural Change and Citizenship -- 6. The Economy and Citizenship -- 7. The Futures of Youth -- 8. Conclusion.
Keywords: Political sociology; Political science; Sociology; Social groups; Political Sociology; Political Science; Sociology of Family, Youth and Aging